Isolation and evaluation of biocontrol agents in controlling anthracnose disease of mango in Thailand - Rungjindamai Nattawut (My University, 2016)
Abstract The agricultural based economy is a core business in Thailand and food export is one of the main sources of income for the Thai population. However, pesticides are overused and misused. As a result there is an urgent need to reduce the use of synthetic chemicals. Biological control offers an alternative to the use of pesticides. Mango ( Mangifera indica L.) is widely planted in Thailand and is one of the major cash crops for international export. However, mango suffers from various diseases especially anthracnose, a fungal disease caused by Colletotrichum gloeosporioides. One hundred and twelve isolates of epiphytic microbes were isolated from healthy leaves and fruits of mangoes; this included 93 and 19 isolates of epiphytic bacteria and yeasts, respectively. They were screened for bioactivity against a pathogenic strain of C. gloeosporioides isolated from diseased mangoes using a dual culture technique. Out of 112 isolates, eight isolates exhibited at least 60% inhibition. These isolates were further screened for their inhibition on mango using fruit inoculation. Two isolates reduced the lesion sizes caused by C. gloeosporioides compared to control treatment. These two isolates, based on phenotypical and biochemical tests, were identified as Bacillus sp. MB61 and Bacillus sp. LB72.
Keywords: Mangifera; Isolation; Plant Pathogens and Fungal Diseases